Dengue Hemorrhagic Fever (DHF) Incidence in the Aur Duri Health Center Work Area in 2024 - Rachel Putri; Rizalia Wardiah; Andree Aulia Rahmat; Rd. Halim; Oka Lesmana S (International Journal of Medicine and Health, 2025)
Background: Dengue Hemorrhagic Fever is a health problem that is very rapidly transmitted, especially in endemic areas in Indonesia, one of which is in Jambi City. Indicators of DHF control activities are measured by the incidence rate per 100,000 population (IR) and the mortality rate (CFR). IR in 2018 was 23.28 per 100,000 population and CFR in 2018 was 0.36%. Although there has been a decrease in CFR every year, the incidence of DHF cases and deaths due to DHF still occur every year in 11 districts/cities in Jambi Province. Method: This study aims to analyze the determinants of the incidence of Dengue Hemorrhagic Fever (DHF) in the Aur Duri Health Center Working Area in 2024. The case control study design, the study was conducted from February to September 2024. This study used primary data from 2024 with a sample of 68 respondents. The variables used are Gender, Residential Density, House Condition, Hanging Clothes Habits, 3M Plus Behavior and Cleaning Water Reservoirs. Conclusion: This study found that the variables related to the incidence of DHF in the Aur Duri Health Center work area in 2024 were the variable of hanging clothes ( p-value = 0.012); 3M Plus Behavior ( p-value = 0.001); and the habit of cleaning water reservoirs ( p-value = 0.007). For the community, it is necessary to always increase self-protection efforts and for the Aur Duri Health Center, it can provide training or movements to eradicate or stop the transmission of DHF.